SPATIALLY DISTRIBUTED MODELING OF PROKARYOTIC COMMUNITY EVOLUTION - S. A. Lashin; E. A. Mamontova; Yu. G. Matushkin (Вавиловский журнал генетики и селекции, 2014)
This paper describes the development of an approach to the simulation of prokaryotic community activity and evolution and the software package «Haploid evolutionary constructor» (http://evol-constructor.bionet.nsc.ru). The initial model with ideal mixing (0D) is expanded to a spatially distributed model (1D). The 0D and 1D poisoner–prey prokaryotic community models are compared. It is shown that the community stability is influenced by the spatial distribution of substrates and prokaryotic cells.